P032 Increased incidence of anti-synthetase syndrome during COVID-19 pandemic. (26th April 2021) - Phillips, Bethan; Martin, James; Rhys-Dillon, Ceril
Abstract: Background/Aims Anti-synthetase syndrome is an idiopathic inflammatory muscle disease, characterised by anti-Jo1 antibodies. Clinical presentation varies between individuals. The diagnosis requires the detection of one or more anti-synthetase antibodies and one or more of the following clinical features: interstitial lung disease, myositis, and inflammatory polyarthritis. Other supporting features include fever, Raynaud's phenomenon, and 'mechanic's hands'. The severity and extent of pulmonary involvement typically determines prognosis. It is a rare disease, with estimated prevalence of 1.5 cases per 100, 000. Our aim is to report an increase in the local prevalence, which coincides with the COVID-19 pandemic. Methods We retrospectively reviewed all new diagnoses of anti-synthetase syndrome made between March and July 2020 at the Royal Glamorgan Hospital. Results 3 new diagnoses of anti-synthetase syndrome were made during the study period. Based on the reported prevalence, we expect to see around 2 cases every 6-months in our hospital (which serves a population of around 300, 000.) Anecdotally, the incidence has been much lower than this previously, and in the experience of three rheumatology consultants working at this hospital, only 6 diagnoses have been made over the last 15 years. This represents a 15-fold increase in the annual diagnosis rate. This anecdotal rise in the number of patients with anti-synthetase syndrome coincides with the COVID-19 pandemic. The incidence of COVID-19 in our health-board during this time period was 666 per 100, 000. This is higher than the national incidence (486 per 100, 000.) All three patients diagnosed with anti-synthetase syndrome had prominent symptoms of shortness of breath, hypoxia and presented on multiple occasions before the final diagnosis was made. Notably, all patients presented acutely unwell with severe symptoms, where ordinarily this diagnosis would be made in the outpatient setting. One case presented with a typical constellation of signs and symptoms. Specifically, progressive shortness of breath with evidence of bilateral interstitial pulmonary disease on imaging, myositis and anti-Jo1 positivity. The remaining two cases presented with primarily lung involvement. In both cases, chest imaging demonstrated extensive bilateral lower lobe pulmonary infiltrates, reported as being in-keeping with COVID-19. Despite repeated negative COVID-19 PCR results, the clinical impression was of probable COVID-19 infection. Following repeated presentations with worsening respiratory symptoms, specialist review was arranged, and ultimately anti-synthetase syndrome was diagnosed. With hindsight, one patient demonstrated extrapulmonary features of Raynaud's phenomenon and 'mechanic's hands'. All cases received methylprednisolone and mycophenolate. Conclusion We report an anecdotal local increase in the incidence of anti-synthetase syndrome, coinciding with the COVID-19 pandemic. The cases described demonstrate an overlap between the presenting clinical features of COVID-19 and anti-synthetase syndrome, and that due to high clinical suspicion of COVID-19 in the context of a global pandemic, some diagnoses of anti-synthetase syndrome may be being missed or delayed. Disclosure B. Phillips: None. J. Martin: None. C. Rhys-Dillon: None.